Effect of pH on elemental sulfur conversion and microbial communities by autotrophic simultaneous desulfurization and denitrification. Issue 23 (1st December 2016) - Xu, Jinlan; Fan, Yimin; Li, Zhixu
ABSTRACT: pH has an important influence on the elemental sulfur accumulated in an autotrophic simultaneous desulfurization and denitrification process. The influent nitrate to sulfide (N/S) mole ratio was set to 0.5, 0.67, 1.0, 1.33 and 2.0 with a 200 mg/L sulfide concentration. The effect of pH on elemental sulfur conversion and microbial communities was studied. Sulfide removal was achieved to the extent of 98% under near-neutral and weak base conditions after 24 h of reaction. The conversion rate of elemental sulfur was 29.41% under the near-neutral condition. The weak base condition led to greater formation of sulfate, and the nitrate used by the microorganisms was transformed mainly to N2 with a removal rate of 96%. Increasing the retention time from 24 to 48 h caused the removal rate of nitrate increased from 63.58% to 90% under the near-neutral condition. Sulfurovum sp. was the functioning bacterial species, and bands 1 and 2 represent different species of Sulfurovum sp. in the system according to the PCR-DGGE analysis of the microbial community structure. The functional bacteria represented by band 1 produced mainly sulfate, but the functional bacteria represented by band 2 produced mainly elemental sulfur.